Peculiarities of the work on vocabulary acquisition in the process of studying the Ukrainian language by foreign students - Rotova, N. (Problems of Engineer-Pedagogical Education, 2020)
Forming an individual's personality as an active and intellectually developed member of society capable of independent realization is a challenge of today. The main characteristic of an individual is language behavior while the main ability is the ability to communicate, especially in the professional sphere. This ability is formed as a result of the development of professional communication skills, which should form the basis of educational activities in the process of mastering the Ukrainian language by foreign students. Vocabulary is required for both productive speaking activity, such as speaking and reading, and receptive speaking activity, such as listening and writing. Depending on the stage of training, a minimum vocabulary is formed and appropriate exercises are selected for semantics and mastering the vocabulary, and a method of mastering Ukrainian vocabulary is developed. When studying vocabulary, the following stages of work with vocabulary are traditionally distinguished: 1) presentation of vocabulary; 2) methodical actions ensuring the assimilation of new vocabulary by foreign students; 3) organization of revision of the learned vocabulary and quality control of assimilation. A communicative or practical goal, which is to teach students the Ukrainian language as a means of communication, is recognized as the leading one at all stages of study. This goal is achieved by solving the following main tasks: I) ensuring the participation of non-philological students in the educational process of higher education institutions, where practical knowledge of the language is necessary primarily for listening to lectures, reading literature, oral presentations at seminars, etc.; 2) preparing students for wide communication in the language environment that surrounds them throughout the study period (which means communication on everyday, socio-cultural, socio-political and educational topics); 3) developing the ability to read professional literature and fiction without using dictionaries. Particular attention needs to be paid to the terminological vocabulary of each specialty, which means special scientific concepts, concepts that shape the professional language environment of a foreign student. The terminological vocabulary performs a semantic and text-forming function, and the term itself acts as a kind of text integrator, integrating and structuring the necessary semantic lexical-grammatical units, ensuring the integrity and logical orientation of the text.